PREVENTING CORRUPTION IN THE BANKING SYSTEM: PROBLEMS AND SOLUTIONS - Jiyanov Bahriddin Ibragimovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article examines and analyzes the issues of preventing corruption by managing the risks of corruption in the banking system.